Chemical constituents, antioxidant, and cytotoxicity of essential oils of Piper arborescens and Piper caninum - Nicholas, Daniel; Fasihuddin Badruddin, Ahmad; Zaini, Assim; Chua, Hun Pin (Penerbit UTM Press, 2019)
Essential oils of the stem bark of Sarawak's wild pepper species namely the Piper arborescens and Piper caninum were extracted by using Clevenger's water distillation method, and analysis using gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectroscopy (GC-MS) have identified a total of 54 and 57 chemical components in the essential oils, respectively. Three major compounds have been identified in the essential oil of Piper arborescens namely the pentadecanal (18.88%), guaiol (11.19%), and β-guaiene (11.12%). In the essential oil of Piper caninum, four main compounds identified were isocaryophyllene (20.60%), (E)-α-bergamotene (13.74%), (E)-isoeugenol (13.46%), and (E,Z)-3,6-nonadien-1-ol (9.35%). Evaluation of antioxidant properties showed the EC50 values of essential oils of Piper arborescens and Piper caninum were 249.30 and 238.70 µg/mL, respectively, indicating low scavenging activity against DPPH as compared to ascorbic acid as standard with EC50 value of 2.72 µg/mL. Cytotoxicity assay showed that average death of Artemia salina brine shrimp in the essential oil of Piper arborescens was higher, with LC50 57.95 µg/mL, as compared to 249.74 µg/mL of essential oil of Piper caninum. The cytotoxic level does not always indicate its outright toxicity but may also indicate the presence of potential natural cytotoxic components, especially in essential oil of Piper arborescens as suggested by Elumba et al. (2013).